ANALISIS DANA DEKONSENTRASI DAN DANA APBD SEKTOR PENDIDIKAN DI PROVINSI JAWA TENGAH 2003 -2011 - Hendra Permana, Leo; Purwanti, Evi Yulia (Diponegoro Journal of Economics, 2013)
Deconcentration a grant from central government to the regions to help increase local government programs are still a central concern: education, health, infrastructure, and others. Deconcentration fund is part of central government expenditure, which consists deconcentration of personnel expenditure, spending on goods, and social assistance.This study aims to analyze the allocation of deconcentration and demonstrate empirically difference deconcentration funds and funds from the budget of the school dropout rate in the province of Central Java. Study of this research uses quantitative data, the type of time series data. Time series data are used from the period 2003-2011. Analysis tools used are different test, to see the difference in the concentration funds and the absence of deconcentration funds with funds from the budget for education and educational development from year to year.Results of the study showed that the concentration funds allocated to primary education, secondaryeducation, early childhood education. The largest allocations to basic education about 90%, different test results indicate that the presence or absence of deconcentration deconcentration has no difference with funds from the province expenditure of the school dropout rate in the province of Central Java.